Christ the liturgy - Daniel, William O. (2013)
This thesis is a constructive work in theology. The aim is to show the centrality of liturgy for theological investigation, exposing how liturgical action at once shapes and gives rise to theological articulation and also manifests an implicit theology. The meaning is in the making, as it were, and this thesis seeks to show the descriptive nature of theology and liturgy as that which makes all theology possible. What is liturgy? Following the earliest usage of leitourgia in the ancient world, and especially as articulated by Saint Paul, Clement of Rome, Ignatius of Antioch, and Irenaeus, I show that the Church’s earliest articulation of liturgical action bears an implied ontology of participation, namely in the singular liturgical action of Christ. Liturgy is not, therefore, to be defined or understood as “the work of the people,” but rather as the “work of the One for the sake of the many,” in which all of creation participates. I argue that the human is to be understood as a liturgical animal who by virtue of her being(-)created is incorporated into the Liturgy God is. I also argue that liturgy names the inter-offering of the Persons of the Trinity, whereby each hypostasis exists as mutually constituting and constituted. The human’s participation in this liturgical action is a participation of the whole person, mediated by the materials and movements involved in the liturgical action—liturgy as the mediation of the divine economy. I also show how late medieval liturgical reforms issue a gradual and unwarranted relegation of the laity’s involvement in the liturgical action. Although inadvertent, this continual extraction of lay participation serves to secularize their role and extract them from the economy to which the liturgy is meant to assimilate. All of this is to expose how the liturgical action, which was vastly influential to the social imaginary of the medieval world, construes and conditions the human more and more along a secular line. Additionally, it is to recover the essential nature of liturgical action for social construction. Indeed, liturgical action as social construction—the embodying of the reciprocal and mutually constituting life of God in whose image the human is created and to whose Being, through Christ the Liturgy, the human has been assimilated, is being-assimilated, and will be assimilated.